Sarcopenia e condições de saúde de idosos institucionalizados - Jorge, Matheus Santos Gomes (2019)
Sarcopenia is an independent clinical condition linked to human aging. It is characterized by loss of muscle mass accompanied by loss of muscle strength and/or function. It is associated with several factors and presents high prevalence among institutionalized elderly. The aim of this dissertation was to determine the prevalence of sarcopenia and associated factors in institutionalized elderly. A cross-sectional population-based study, which was part of a project entitled “Padrões de Envelhecimento e Longevidade: Aspectos Biológicos, Educacionais e Psicossociais de Idosos Institucionalizados”, approved by the Research Ethics Committee of the University of Passo Fundo under protocol number 2.097.278. Were evaluated 479 elderly people living in 18 long-term care facilities in the municipalities of Passo Fundo/RS, Bento Gonçalves/RS and Carazinho/RS. The elderly were evaluated for sarcopenia (criteria of the European Working Group on Sarcopenia in Older People), risk of sarcopenia (SARC-CalF questionnaire), demographic variables, health conditions, anthropometric variables, cognitive status (Mini Mental State Examination), nutritional status (Mini Nutritional Assessment), fragility (Fried phenotype) and functional capacity (Katz Scale). In the statistical analysis, were used the descriptive statistics, the association tests and the crude and adjusted analysis by the Poisson regression with robust variance. The level of significance was 5%. As results, this dissertation presented two scientific productions titled “Prevalence of sarcopenia and associated factors in institutionalized elderly” and “Risk of sarcopenia in institutionalized elderly”. The articles were drafted in accordance with the norms of international journals to which they will be submitted and where the results can be found in full. In summary, this study demonstrates that elderly present a high prevalence of sarcopenia (associated with longevity, thinness, reduced calf circumference and malnutrition), especially of the severe type, and a high risk of sarcopenia (associated with the accident vascular disease, Parkinson's disease, dysphagia and frailty). In addition, research on the prevalence of sarcopenia in institutionalized elderly is relatively scarce and the SARC-CalF questionnaire is consistent and useful for this population. This dissertation contributes to the understanding of sarcopenia in elderly people living in longterm care facilities, in order to promote the development of interdisciplinary strategies and public policies in this context.